Komunikasi Dakwah Islam pada Masyarakat Milenial di Era Globalisasi - Adhitya Ridwan Budhi Prasetyo Nugroho; Umi Halwati (ICODEV: Indonesian Community Development Journal, 2023)
With the emergence of the internet as a new medium of communication, Islamic da'wah can take advantage of new possibilities in today's interconnected world. Cyberdakwah discourse is one example of how the internet is used to amar ma'ruf nahi munkar. the internet as a new space for the work of Islamic da'wah. The Internet has made it possible for media to reach audiences of various races and religions. The internet and other forms of media can also be used to dispel common misconceptions about Islamic beliefs and practices by presenting the human face of the religion. The method in this study is qualitative with a library study approach. The results of the study show that Cyberdakwah is a phenomenon of using the internet to convey information and messages of Islamic teachings. The use of the internet as a medium of da'wah is accompanied by various advantages and disadvantages. Positively, the internet is a new medium for Islamic da'wah that can transmit messages of Islamic teachings effectively, openly, easily accessible, and with a broad reach both in terms of region, space and time. Negatively, the open and access-free character of the internet allows for the mixing of the sacred values ​​of Islamic teachings with various intakes of information that are not clear on the credibility of the conveyer, have hoaxes and hatespeech tones, as well as information in the name of Islam for specific purposes.